Increased Risk of Acute Coronary Syndrome in Patients With Chronic Pancreatitis: A Nationwide Cohort Analysis. Issue 20 (May 2016) - Hsu, Ming-Tse; Lin, Cheng-Li; Chung, Wei-Sheng
Abstract : Abstract: Chronic inflammation may promote development of coronary heart disease. Studies on the relationship between chronic pancreatitis (CP) and cardiovascular diseases are scant. We conducted a nationwide retrospective cohort study to determine the risk of acute coronary syndrome (ACS) in patients with CP. We randomly selected a comparison cohort of individuals without CP from the Taiwan National Health Insurance Research Database (N = 23.74 million) and frequency-matched them with patients with CP from 2000 to 2010 in a 1:4 ratio according to age, sex, and index year. The follow-up period lasted from the index date of the new CP diagnosis to the date of ACS diagnosis, censoring, or the end of 2011. We analyzed the risk of ACS by using Cox proportional-hazard models. In total, 17, 405 patients with CP and 69, 620 individuals without CP were followed for 84, 430 and 417, 426 person-years. Most patients with CP were men, and the mean age of the patients was 48.3 ± 15.0 years. The overall ACS incidence was 2.15-fold higher in the CP cohort than in the non-CP cohort (4.89 vs 2.28 per 10, 000 person-years) with an adjusted hazard ratio (aHR) of 1.40 (95% confidence interval [CI] 1.20–1.64). Compared with individuals without CP, patients with CP aged ⩽39 years exhibited the highest risk of ACS (aHR 2.14, 95% CI 1.13–4.02), followed by those aged 40 to 54 years (aHR 1.66, 95% CI 1.23–2.24) and those aged 55 to 69 years (aHR 1.53, 95% CI 1.15–2.03). CP may become an independent risk factor for ACS.